A disaggregated-level analysis of the relationship among energy production, energy consumption and economic growth: Evidence from China. (1st March 2020) - Ur Rahman, Zia; Iqbal Khattak, Shoukat; Ahmad, Manzoor; Khan, Anwar
Abstract: The purpose of this study is to explore the relationship between energy production, energy consumption, and gross domestic product (GDP) growth in China for the period 1981–2016 (at the disaggregate level). The results of the Hatemi-J cointegration and structural-break tests supported long-term co-integration in the consumption and production of coal, oil, and natural gas. Based on the three models (coal, oil, and natural gas) of energy production and consumption, the fully-modified least square (FMOLS) method results confirmed the presence of long-term positive impact of the consumption and production of coal, oil, and natural gas on GDP growth. The CCR model estimations for robustness were found to be consistent with the FMLOS estimations. The vector error correction mechanism (VECM) based Granger-causality tests identified a one-way causality run from coal production and coal consumption to GDP growth; from GDP growth to gas consumption (supporting conservation hypothesis); from natural gas production to natural gas consumption; and from oil production and oil consumption to GDP growth. The paper draws important policy implications for theory, research and practice. Highlights: Energy production, energy consumption and economic growth were examined in China. The Hatemi-J and FMOLS tests supported long term co-integration among variables. Both energy consumption and production positively affect economic growth. A one-way Granger causality observed from coal and oil to economic growth. A one-way Granger causality observed from economic growth to gas consumption.